2020
DOI: 10.7717/peerj.10435
|View full text |Cite
|
Sign up to set email alerts
|

Neither ant dominance nor abundance explain ant-plant network structure in Mexican temperate forests

Abstract: Background Ant-plant mutualistic networks tend to have a nested structure that contributes to their stability, but the ecological factors that give rise to this structure are not fully understood. Here, we evaluate whether ant abundance and dominance hierarchy determine the structure of the ant-plant networks in two types of vegetation: oak and grassland, in two temperate environments of Mexico: Flor del Bosque State Park (FBSP) and La Malinche National Park (MNP). We predicted that dominant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…These findings are consistent with those found in the scientific literature; several studies with various taxa show that conversion of natural habitats and intensification of agrosystems leads to species reduction and changes in composition, as well as changes in the structure and functioning of the ecosystem. [36][37][38] examples in the literature of how conversion of native areas for food production affected the local fauna, perhaps the best studied is that of coffee production in Latin America, according to which a reduction in the diversity of ants was noted in a review by Eldridge et al 39 However, the magnitude of this reduction was dependent on the type of land management (monoculture of coffee or coffee in the shade of native trees), in addition to considering ecological services. 14,40 Similar patterns of reduction in ant diversity or richness in planting systems were also found in the Amazon 41 , Argentina 42,43 , Australia 44 , Africa 45 , and China 46 .…”
Section: Effects On Richnessmentioning
confidence: 99%
“…These findings are consistent with those found in the scientific literature; several studies with various taxa show that conversion of natural habitats and intensification of agrosystems leads to species reduction and changes in composition, as well as changes in the structure and functioning of the ecosystem. [36][37][38] examples in the literature of how conversion of native areas for food production affected the local fauna, perhaps the best studied is that of coffee production in Latin America, according to which a reduction in the diversity of ants was noted in a review by Eldridge et al 39 However, the magnitude of this reduction was dependent on the type of land management (monoculture of coffee or coffee in the shade of native trees), in addition to considering ecological services. 14,40 Similar patterns of reduction in ant diversity or richness in planting systems were also found in the Amazon 41 , Argentina 42,43 , Australia 44 , Africa 45 , and China 46 .…”
Section: Effects On Richnessmentioning
confidence: 99%
“…(Lara et al, 2020) and the other at 2300–2900 m a.s.l. (Juárez‐Juárez et al, 2020). It is well known that ant‐plant interactions may vary in relation to temperature, precipitation, and temporal fluctuations in the availability of plant‐provided resources (Lange et al, 2017; Rico‐Gray et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…At high elevations, it has been observed that the ant‐plant interaction networks that involve floral and EFN and forage substrate are reduced in the number of interacting species (small network size), possibly due to climatic conditions and plant resources. However, despite being networks with small size, these sites at high elevations have a nested structure (Juárez‐Juárez et al, 2020; Lara et al, 2020). In specialised networks, such as ant‐plant interactions involving myrmecophytes, a study performed by Plowman et al (2017) showed that the networks become more connected and less specialised at higher elevations, which directly affect the benefits obtained from this association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenolepis imparis is a dominant ant found foraging on practically all plants in the oak forest of FBSP. This ant is characterized by its adaptation to cold environments, aggressive behavior, and ability to forage at low temperatures ( Wheeler, 1930 ; Lynch, Balinsky & Vail, 1980 ; Fellers, 1989 ; Andersen, 1997 ; Juárez-Juárez et al, 2020 ). Prenolepis imparis depends heavily on honeydew at the study site, with a marked seasonality to its foraging; it is almost exclusively found collecting honeydew on plants in the rainy season (Cuautle per.…”
Section: Discussionmentioning
confidence: 99%